Brother sun, sister moon : the life and stories of St. Francis - Mayo, Margaret (Little, Brown, and Co., Boston, Mass, 2000)
The story of St. Francis of Assisi, who rejected his wealthy background to lead a life of poverty, good works, and kindness to animals.
New York Tim
Kirkus
Horn Book
Sch Libr Jnl
740
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; Christian saints -- Biography; Assisi (Italy) -- Biography